Are the economically active more deserving? - Gaffney, B. (1995)
OBJECTIVE--To investigate the possibility of an association between the duration of medical treatment before coronary angiography and demographic and non-clinical factors. DESIGN--A systematic review of a random sample of 500 patients undergoing their first angiographic assessment. SUBJECTS--500 cases were selected randomly from patients investigated in 1991 at the two catheterisation centres in Northern Ireland. MAIN OUTCOME MEASURES--The duration of medical management before angiography. RESULTS--346 had elective and 154 urgent catheterisation. The duration of medical management was adjusted for both case mix (age at onset, body mass index, angina grade, history of myocardial infarction, history of hypertension, diabetes or hyperlipidaemia, treatment intensity) and other demographic variables (sex, smoking status, an indicator of "deprivation", and distance of the patient's area of residence from the hospital). After this adjustment the mean duration of medical management before angiography was twice as long for economically inactive patients as for those who were economically active. In a multiple regression, the relevant beta coefficient was 0.44 (95% confidence interval 0.33 to 0.58, P < 0.0001). CONCLUSIONS--These results suggest that, in making discretionary decisions about when to refer patients with angina for revascularisation assessment, doctors may be influenced by non-clinical factors unrelated to disease severity.